Penegakan Hukum Terhadap Pelaku Tindak Pidana Eksploitasi Anak Yang Dijadikan Pengemis Di Wilayah Hukum Kepolisian Resor Kota Pekanbaru - Ramayana Ramayana; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Children are vulnerable to becoming victims in a crime. One of the crimes against children is the exploitation of children who are made beggars, where children are employed by begging on the streets. In the child protection law, it is clear that there are prohibitions and criminal sanctions against perpetrators who exploit children, but there are still many cases of exploitation of children not followed up by law enforcers. Law enforcers should take firm action against child exploiters who become beggars based on Law Number 35 of 2014 concerning Protection. The author's research objectives are: To find out the law enforcement against the offenders of child exploitation crimes that are used as beggars, and the factors that hinder the law enforcement of the perpetrators of child exploitation crimes that are used as beggars in the Kepolresta Pekanbaru legal area.In this study the authors use the method of sociological legal research that is research that wants to see the correlation between law and society, this study was conducted in the jurisdiction of the Pekanbaru police resort town, while the population and sample are all of the parties related to the problem under study, in this study the data source used are primary data sources, secondary data, and Tertiary Legal Materials, data collection techniques in this paper that is by conducting interviews and library research, and the authors analyze the data using deductive methods namely ways of thinking that draw conclusions from a statement or proposition that is general nature into a statement that is special.From the results of the author's research, it can be concluded that; first, law enforcement against child exploitation perpetrators who are beggars in the Pekanbaru city police jurisdiction is less effective because the perpetrators of child exploitation criminals who are used as beggars never process law. Second, the servant factors faced by the police in upholding the law are the lack of awareness and awareness of the law of the community, factors of law enforcement officials, facilities and infrastructure, culture and morals of the communityKeywords: Law Enforcement - Criminal Acts - Child Exploitation